2019
DOI: 10.3389/fphar.2019.00978
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin Inhibits Mesangial Cell Proliferation and Inflammatory Response in Rats With Mesangial Proliferative Glomerulonephritis Through PI3K/AKT/GSK-3β Pathway

Abstract: Mesangial proliferative glomerulonephritis (MPGN) is the most common type of chronic kidney disease in China, characterized by mesangial cell proliferation and inflammatory response. Paeoniflorin, an effective composition extracted from Radix Paeoniae Alba, has been used for various kinds of kidney diseases. However, there are no studies reporting the effects of paeoniflorin on MPGN. The present study aims to investigate whether paeoniflorin plays a role in MPGN and confirm the underlying molecular mechanisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…As long-established cell lines in literature, mesangial cells and podocytes are important biological samples to determine the best reference gene -many researchers in the field are focused on these structures (42)(43)(44)(45)(46)(47) and the data provided by our work could potentially influence many studies, providing support to avoid wrong interpretation of results and its influence in downstream analysis and further conclusions.…”
Section: Discussionmentioning
confidence: 87%
“…As long-established cell lines in literature, mesangial cells and podocytes are important biological samples to determine the best reference gene -many researchers in the field are focused on these structures (42)(43)(44)(45)(46)(47) and the data provided by our work could potentially influence many studies, providing support to avoid wrong interpretation of results and its influence in downstream analysis and further conclusions.…”
Section: Discussionmentioning
confidence: 87%
“…As long-established cell lines in the literature, mesangial cells and podocytes are important biological samples to determine the best reference gene-many researchers in the field are focused on these structures [54][55][56][57][58][59], and the data provided by our work could potentially influence many studies, providing support to avoid incorrect interpretation of results and their influence in downstream analysis and further conclusions.…”
Section: Plos Onementioning
confidence: 95%
“…Recently, studies have reported that paeoniflorin (PF), an extract of paeonia lactiflora root, inhibits the proliferation of a variety of cells, such as human mesangial cells (Liu et al 2019 ), B cells (Zhang et al 2015 ) and vascular smooth muscle cells (Fan et al 2018 ). However, the effect of PF on the proliferation and the polarization of macrophages are not yet clear.…”
Section: Introductionmentioning
confidence: 99%